The Effect of a Proposed Mindfulness-Based Strategy on Developing Deep Text Comprehension Skills among First-Grade Intermediate Students in Arabic Language Subject - Aqeel Rasheed Abdul-Shahid Al-Asadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Abstract:       The aim of the research was to: (identify the deep text comprehension skills necessary for first-grade intermediate students, develop a strategy based on mindfulness, and determine the effect of this strategy on developing deep text comprehension skills among first-grade intermediate students in reading and text lessons). To achieve the research objectives, the researcher adopted two approaches: a descriptive approach to identify the skills and develop the strategy, and an experimental approach to examine the effect of the strategy on skill development.The research population consisted of public intermediate day schools in Babil Governorate, Iraq, during the academic year 2024–2025. The research sample included 63 students, with 31 students in the experimental group and 32 in the control group, selected randomly. The researcher ensured the equivalence of both groups statistically in terms of age, parental education level, and IQ test scores. The experiment lasted for an entire academic semester, at the end of which the researcher administered a Deep Text Comprehension Test that had been previously validated and verified for reliability.The results showed that the students in the experimental group who were taught using the proposed strategy outperformed those in the control group who were taught using traditional methods. The researcher recommended adopting the proposed strategy in teaching reading, and suggested several follow-up studies, including one to examine the relationship between mindfulness and reading awareness.DOI: https://doi.org/10.54633/2333-024-056-029